2017
DOI: 10.5194/hess-21-3859-2017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of rainfall and their effects on hydrological response in urban areas – a review

Abstract: Abstract. In urban areas, hydrological processes are characterized by high variability in space and time, making them sensitive to small-scale temporal and spatial rainfall variability. In the last decades new instruments, techniques, and methods have been developed to capture rainfall and hydrological processes at high resolution. Weather radars have been introduced to estimate high spatial and temporal rainfall variability. At the same time, new models have been proposed to reproduce hydrological response, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
146
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(170 citation statements)
references
References 140 publications
(276 reference statements)
2
146
0
5
Order By: Relevance
“…Variogram analysis was conducted theoretically to describe temporal (or spatial) variability as the characteristic scale, which was defined as the temporal (or spatial) distance by which two individual points show statistical independence [3]. Based on this method, Berne et al [10] proposed the relationship between the required characteristic scales of rainfall and urban catchments, and then derived the required rainfall resolution for urban hydrological applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variogram analysis was conducted theoretically to describe temporal (or spatial) variability as the characteristic scale, which was defined as the temporal (or spatial) distance by which two individual points show statistical independence [3]. Based on this method, Berne et al [10] proposed the relationship between the required characteristic scales of rainfall and urban catchments, and then derived the required rainfall resolution for urban hydrological applications.…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, Singh [2] summarized how the hydrograph is affected by the temporal and spatial distribution of rainfall and identified that the influence of rainfall also depends on watershed characteristics. Rainfall variability makes it important to adopt an appropriate rainfall resolution to model hydrological response, especially in urban catchments with short response time [3,4]. In particular, for small urban catchments with drainage area no more than 10 km 2 , the temporal resolution of rainfall (TRR), rather than the spatial resolution of rainfall (SRR), has larger effect on hydrodynamic modelling [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…An important question concerns how the peak discharge and the volume of a flood depend on the intensity and track of the triggering precipitation events, i.e. the spatio-temporal pattern of precipitation (Adams et al, 2012;Bruni et al, 2015;Cristiano et al, 2017;Emmanuel et al, 2015Emmanuel et al, , 2016OchoaRodriguez et al, 2015;Paschalis et al, 2014;Rafieeinasab et al, 2015;Zhang and Han, 2017). In addition to the storm track dynamics, the peak flow depends on the watershed characteristics (Singh, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, uncertainties in the economic models used to estimate flood losses and flood damages are relevant (de Moel et al, 2015). Herein, the input data, the choice of the impact indicators, the scale, and the vulnerability models are relevant sources of uncertainty (Ward et al, 2013;Apel et al, 2008;Merz and Thieken, 2009;de Moel and Aerts, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation